2016
DOI: 10.31887/dcns.2016.18.1/pkalivas
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal circuitry in regulating diseases characterized by intrusive thinking

Abstract: Intrusive thinking triggers clinical symptoms in many neuropsychiatric disorders. Using drug addiction as an exemplar disorder sustained in part by intrusive thinking, we explore studies demonstrating that impairments in corticostriatal circuitry strongly contribute to intrusive thinking. Neuroimaging studies have long implicated this projection in cue-induced craving to use drugs, and preclinical models show that marked changes are produced at corticostriatal synapses in the nucleus accumbens during a relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…However, emerging evidence exists, pointing to alterations in corticostriatal functioning associated with both state and trait PC [ 22 , 58 , 72 ]. In line with the proposal of Kalivas and Kalivas [ 73 ], further investigations of the corticostriatal involvement in the maintenance of PC and its effects on reward-related behavior could forecast therapeutic impact on many disorders, all afflicted by this maladaptive symptom.…”
Section: Limitations and Conclusionsupporting
confidence: 57%
“…However, emerging evidence exists, pointing to alterations in corticostriatal functioning associated with both state and trait PC [ 22 , 58 , 72 ]. In line with the proposal of Kalivas and Kalivas [ 73 ], further investigations of the corticostriatal involvement in the maintenance of PC and its effects on reward-related behavior could forecast therapeutic impact on many disorders, all afflicted by this maladaptive symptom.…”
Section: Limitations and Conclusionsupporting
confidence: 57%
“…NAC may exert potential therapeutic effects through the amelioration of all of those processes [ 130 ] No controlled studies published examining NAC treating PTSD alone. One small RCT (N=35) investigating NAC and CBT treating PTSD and SUD found no significant improvement in PCL-M and BDI [ 129 ] Substance-use disorders Reduction of intrusive thoughts (cravings) through manipulation of the glutamatergic system in the nucleus accumbens [ 135 ] Multiple small RCTs investigating NAC in treating multiple substance use disorders, majority demonstrating no significant improvement over placebo Neurocognitive disorders Neurocognitive disorders are associated with increased neuroinflammation, mitochondrial dysfunction, and increased oxidative stress, NAC may exert potential therapeutic effects through the amelioration of all of those processes [ 188 ] Multiple small studies with mixed results Chronic pain Reduction of increased oxidative stress associated with chronic pain [ 198 ] Modulation of abnormal glutamatergic activity in the pain matrix [ 14 ] Meta-analysis of controlled and non-controlled trials (combined N=863) found no significant effect of NAC in treating chronic pain [ 198 ] ASD Autism Spectrum Disorder, ABC Aberrant Behaviour Checklist, RCT randomized controlled trial, PANSS Positive and Negative Syndrome Scale, SOPS Scale of Prodromal Symptoms, MADRS Montgomery Åsberg Depression Rating Scale, YMRS Young Mania Rating Scale, BDRS Bipolar Depression Rating Scale, HDRS Hamilton Depression Rating Scale, CGI-S Clinical Global Impressions-Severity, SLICE-LIFE Streamlined Longitudinal Interview Clinical Evaluation from the Longitudinal Interval Follow-up Evaluation, LIFE-RIFT Longitudinal Interval Follow-up Evaluation-Range of Impaired Functioning, GAD generalised anxiety disorder, SP social phobia, OCD obsessive compulsive disorder, MGH-HPS Massachusetts General Hospital Hair Pulling Scale, NE-YBOcCS Yale-Brown Obsessive Compulsive Scale for Excoriation Disorder, PTSD post-traumatic stress disorder, CBT cognitive behavioral therapy, SUD substance-use disorder, PCL-M PTSD Checklist-Military, BDI Beck Depression Inventory …”
Section: Discussionmentioning
confidence: 99%
“…Through direct effects on cysteine/glutamate exchange and by promoting astroglial glutamate uptake, which are reduced in animal models of SUD, NAC restores the homeostatic relationship in glutamate transport and release between neurons and astroglia. The action of NAC in the nucleus accumbens reduces substance-associated intrusive thoughts (e.g., cravings or urges to use), thereby allowing more adaptive behaviors to emerge to help maintain abstinence from use [ 135 ]. In a rat model, NAC reduced stress-induced alcohol use and cue-related reinstatement of alcohol, heroin, nicotine, cannabis, and cocaine use [ 136 ].…”
Section: Substance-use Disordersmentioning
confidence: 99%
“…The STR is another main reward-associated brain region that plays an important role in regulating motivation, habitual action and learning, goal-directed behaviors, and cognition, and studies have shown that alcohol exposure alters striatal function [ 11 , 12 , 20 , 64 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results showed that both AEA and 2-AG content increased in the anterior STR after mice were exposed to both mSPS and CIE compared to mice exposed to mSPS only.…”
Section: Discussionmentioning
confidence: 99%